Three-dimensional Middle Infrared Spectroscopy Study on Crystalline and Amorphous Structures and Thermostability of Corn, Wheat, and Pea Starch - KONG Xiao-mei; DU Lin-nan; JIANG Meng-wei; CHAI Jia-xin; CHANG Mei-ling; ZHANG Yong; CHANG Ming; XU Yuan-yuan (Liang you shipin ke-ji)
The structure and thermal denaturation of three types of starch, including corn starch, wheat starch, and pea starch, were studied using one-dimensional mid infrared (MIR) spectroscopy, temperature dependent one-dimensional MIR spectroscopy and two-dimensional MIR spectroscopy. The results showed that the infrared absorption modes of the three types of starch structures mainly include the C—O stretching vibration mode (vC—O starch), and all three types of starch contain crystalline and amorphous structures. The structures of the three types of starch are sensitive to temperature changes, with the amorphous structure being the first to change and the crystalline structure being relatively stable. Under thermal disturbance factors, there are strong intramolecular interactions between the amorphous structures of wheat. This study expands the research scope of third-order mid infrared spectroscopy (including one-dimensional mid infrared (MIR) spectroscopy, temperature dependent one-dimensional MIR spectroscopy, and two-dimensional MIR spectroscopy) in the structure and thermal denaturation of crystalline/amorphous regions of starch.